Integration of Local Wisdom Haul Guru Sekumpul Martapura in the Development of Islamic Education Management - Musyarapah Musyarapah; Noorazmah Hidayati; Helmiannoor Helmiannoor (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
The annual Guru Sekumpul Haul in Martapura, South Kalimantan, is a religious event with deep local wisdom. This tradition is not only related to the commemoration of the death of Guru Sekumpul, KH Muhammad Zaini Abdul Ghani, but also implies various social, cultural and religious values lived by the Banjar people. The people who enthusiastically welcome this haul show the spirit of gotong royong in its organisation, by providing free accommodation, consumption and lodging for the pilgrims. This research aims to identify how the integration of local wisdom values contained in Guru Sekumpul's haul in the development of Islamic education management. Using a qualitative approach with a case study, this research found that the haul of Guru Sekumpul has a significant impact in strengthening the relationship, strengthening the sense of community, and becoming a religious tourism attraction that supports the local economy. In addition, this activity also reflects local traditions and customs that have been maintained for generations. This Haul is not just a religious commemoration, but also has a profound positive impact on the development of Islamic education management on strengthening religious, social values, curriculum alignment, leadership development, improving the relationship between formal and informal education, community empowerment in education management and community development.